MOTIVASI PENERJEMAHAN BUKU BERBAHASA ARAB (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
The translation of Arabic books in Indonesia can’t be separated from somemotives. At least, there are five motives of the translation, i.e. religious,educational, economical, ideological, and prevocational motives. Religiousmotive can be seen in translator’s statements that his/her works is aimedto get blessing from Allah. Educational motive can be seen in the fact thatthese works are aimed to give Islamic knowledges to muslim community.Economical advantages are the most powerfull motivations that publisherstry to get by publishing Arabic translations books. In other hand, ideologicalmotive is one of factors that the translators or publishers want to propagate their Islamic ideological among Indonesian muslim community by mean of their translation works. Prevocational motive can be seen in translatorintention to stimulate critical Islamic discourse in Indonesia by mean oftranslating Arabic books written by some Middle East critical writers.